Rewards and Work Environment as Predictors of Employee Job Satisfaction at PTPN IV Regional I - Wahyu Pinastia Ningrum; Muhammad Irwan Padli Nasution; Muhammad Ikhsan Harahap (Research Synergy Foundation, 2026)
Employee job satisfaction remains an important human resource management issue in plantation companies because employees work under diverse operational and environmental conditions that influence their perceptions of organizational rewards and workplace quality. Despite extensive research on job satisfaction, empirical evidence regarding the relationships between rewards, work environment, and employee job satisfaction in Indonesia's plantation sector remains limited. Therefore, this study examined whether rewards and work environment are associated with employee job satisfaction at PT Perkebunan Nusantara IV Regional I Bandar Betsy. This study employed a quantitative explanatory survey involving 80 employees selected through stratified random sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression. The findings indicate that rewards are positively and significantly associated with employee job satisfaction. Likewise, the work environment is positively and significantly associated with employee job satisfaction. Furthermore, rewards and work environment jointly explain a substantial proportion of the variation in employee job satisfaction. These findings support the applicability of Herzberg's Two-Factor Theory in the plantation-sector context by demonstrating that both organizational rewards and workplace conditions are important predictors of employee job satisfaction. Practically, the findings provide empirical evidence that may assist the management of plantation companies in developing fair reward systems and supportive workplace conditions to enhance employee job satisfaction.